Risk of human‐to‐wildlife transmission of SARS‐CoV‐2 - Gryseels, Sophie; De Bruyn, Luc; Gyselings, Ralf; Calvignac‐Spencer, Sébastien; Leendertz, Fabian H.; Leirs, Herwig (Mammal review, 2021)
It has been a long time since the world has experienced a pandemic with such a rapid devastating impact as the current COVID‐19 pandemic. The causative agent, severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), is unusual in that it appears capable of infecting many different mammal species. As a significant proportion of people worldwide are infected with SARS‐CoV‐2 and may spread the infection unknowingly before symptoms occur or without any symptoms ever occurring, there is a non‐negligible risk of humans spreading SARS‐CoV‐2 to wildlife, in particular to wild non‐human mammals. Because of SARS‐CoV‐2’s apparent evolutionary origins in bats and reports of humans transmitting the virus to pets and zoo animals, regulations for the prevention of human‐to‐animal transmission have so far focused mostly on these animal groups. We summarise recent studies and reports that show that a wide range of distantly related mammals are likely to be susceptible to SARS‐CoV‐2, and that susceptibility or resistance to the virus is, in general, not predictable, or only predictable to some extent, from phylogenetic proximity to known susceptible or resistant hosts. In the absence of solid evidence on the susceptibility and resistance to SARS‐CoV‐2 for each of the >6500 mammal species, we argue that sanitary precautions should be taken by humans interacting with any other mammal species in the wild. Preventing human‐to‐wildlife SARS‐CoV‐2 transmission is important to protect these animals (some of which are classed as threatened) from disease, but also to avoid establishment of novel SARS‐CoV‐2 reservoirs in wild mammals. The risk of repeated re‐infection of humans from such a wildlife reservoir could severely hamper SARS‐CoV‐2 control efforts. Activities during which direct or indirect interaction with wild mammals may occur include wildlife research, conservation activities, forestry work, pest control, management of feral populations, ecological consultancy work, management of protected areas and natural environments, wildlife tourism and wildlife rehabilitation in animal shelters. During such activities, we recommend sanitary precautions, such as physical distancing, wearing face masks and gloves, and frequent decontamination, which are very similar to regulations currently imposed to prevent transmission among humans. We further recommend active surveillance of domestic and feral animals that could act as SARS‐CoV‐2 intermediate hosts between humans and wild mammals. SARS‐CoV‐2, the highly transmissible novel coronavirus in humans, has a strikingly broad potential host range. We review the risk and potential impact of human‐to‐wildlife transmission of SARS‐CoV‐2. As demonstrated by several observations of humans transmitting SARS‐CoV‐2 to felids, dogs and mink, and by numerous animal and in vitro infection experiments, it is clear the virus is able to infect and be transmitted among a wide range of distantly related mammal species. If SARS‐CoV‐2 was to infect and spread among wild mammals, it could potentially cause disease in some mammal populations, in turn further endangering already threatened species or populations. A new animal reservoir of SARS‐CoV‐2 could be established if the virus were to be sustainably transmitted among some mammalian populations or communities. Such a reservoir could repeatedly source new outbreaks in humans and other animals and would severely hamper control measures of the pandemic. We therefore urge people to take sensible sanitary precautions when in direct or indirect contact with any wild or feral mammal species to prevent human‐to‐wildlife transmission of SARS‐CoV‐2. Controlling transmission routes from humans to wildlife via domestic, commensal or feral mammals acting as intermediate hosts will likely depend on early and active surveillance of these mammals.